# Aptitude - Surds and Indices - Discussion

Discussion Forum : Surds and Indices - General Questions (Q.No. 2)
2.
 If a x - 1 = b x - 3 , then the value of x is: b a
 1 2
1
2
 7 2
Explanation:

 Given a x - 1 = b x - 3 b a

 a x - 1 = a -(x - 3) = a (3 - x) b b b

x - 1 = 3 - x

2x = 4

x = 2.

Discussion:
26 comments Page 1 of 3.

URVASHI said:   4 years ago
Simply Cross Multiply them a with a and b with b.

It becomes;

[a ^(x-1) ][a^(x-3)] = [b^(x-1)][b^(x-3)].
Power will get add on both sides.
Then,
a^(2x-4) = b^(2x-4),
Simply, x=2.
(2)

SuryaTeja said:   4 years ago
Am not getting this, please explain in detail.
(2)

Panther said:   6 years ago
How come 4?
(2)

Frazer Juma said:   5 years ago
Thanks, guys! I understood very well.
(1)

Ashish said:   6 years ago
I am not geting. How to solve this?
(1)

Sachin d said:   7 years ago
Thanks @Heman.
(1)

Husain SR said:   8 years ago
Here (a/b)^x-1 and (b/a)^x-3 now if we reciprocal b/a to a/b then there is negative sign on it.
(a/b)^-(x-3).

Let compare thier powers;

x - 1 = -(x - 3).
x - 1 = -x + 3
x + x = 1 + 3.
2x = 4
(1)

Lawal Adetunji said:   7 years ago

Yesubabu said:   3 years ago
@Urvashi.

You are absolutely right, Thanks for explaining.

Shweta said:   7 years ago
@Husain.

When you compare the power then , x-1=-x-3.
Then how you change the sign of ,x-1=x+3?